Fiscal policy and fiscal fragility: Empirical evidence from the OECD - Makram El-Shagi; Gregor von Schweinitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
In this paper, we use local projections to investigate the impact of consolidation shocks on GDP growth, conditional on the fragility of government finances. Based on a database of fiscal plans in OECD countries, we show that spending shocks are less detrimental than tax-based consolidation. In times of fiscal fragility, our results indicate strongly that governments should consolidate through surprise policy changes rather than announcements of consolidation at a later horizon.
urn:nbn:de:gbv:3:2-107570
Keywords: E62; H63; 330; fiscal multipliers; fiscal consolidation; local projections